Effects of Usag-1 and Bmp7 deficiencies on murine tooth morphogenesis. Issue 1 (December 2016) - Saito, Kazuyuki; Takahashi, Katsu; Asahara, Masakazu; Kiso, Honoka; Togo, Yumiko; Tsukamoto, Hiroko; Huang, Boyen; Sugai, Manabu; Shimizu, Akira; Motokawa, Masaharu; Slavkin, Harold; Bessho, Kazuhisa
Abstract Background Wnt5a andMrfzb1 genes are involved in the regulation of tooth size, and their expression levels are similar to that ofBmp7 during morphogenesis, including during the cap and early bell stages of tooth formation. We previously reported thatUsag-1 -deficient mice form supernumerary maxillary incisors. Thus, we hypothesized that BMP7 and USAG-1 signaling molecules may play important roles in tooth morphogenesis. In this study, we established double genetically modified mice to examine the in vivo inter-relationships betweenBmp7 andUsag-1 . Results We measured the volume and cross-sectional areas of the mandibular incisors using micro-computed tomography (micro-CT) in adultBmp7 - andUsag-1 -LacZ knock-in mice and their F2 generation upon interbreeding. The mandibular incisors of adultBmp7 +/− mice were significantly larger than those of wild-type (WT) mice. The mandibular incisors of adultUsag-1 −/− mice were the largest of all genotypes examined. In the F2 generation, the effects of these genes were additive;Bmp7 +/− was most strongly associated with the increase in tooth size using generalized linear models, and the total area of mandibular supernumerary incisors ofUsag-1 −/−Bmp7 +/− mice was significantly larger than that ofUsag-1 −/−Bmp7 +/+ mice. At embryonic day 15 (E15), BrdU assays demonstrated that the labeling index ofBmp7 +/− embryos was significantly higher than that of WT embryos in the cervical loop. Additionally, the labeling index ofUsag-1 −/− embryos was significantly the highest of all genotypes examined in dental papilla. Conclusions Bmp7 heterozygous mice exhibited significantly increased tooth sizes, suggesting that tooth size was controlled by specific gene expression. Our findings may be useful in applications of regenerative medicine and dentistry.